IDENTIFICATION OF WILD PLANTS AS A REFUGIA PREDATOR AND ORANGE PLANT PARASITOID (Citrus grandis) IN JERUK DESA KERONGKONG DISTRICT LOMBOK TIMUR - Muliawan, Wawan (Cocos Bio, 2020)
Control of Plant Pest Organisms by using synthetic pesticides has a negative impact on the garden. Some of these impacts include environmental pollution, the emergence of "biotypes" that are resistant and resurgent, the natural enemy population decreases and is less efficient, the loss of several types of plants that are potential to be used as refugia plants, expensive control costs, and a decrease in the quantity and quality of production of cultivated plants. In this case, action needs to be taken that can be used as an alternative solution to the problem of pest attacks. Wild plants have the potential as refugia for pest insect predators. Refugia plants are types of plants around plants that can provide shelter, additional feed sources, resting places, and reproductive sites (Nentwig, 1998; Wratten et al., 1998; Sosromarsono and Untung, 2000 in Rahman, 2010). Refugia plants in the field of agriculture generally refer to the types of plants and plants that have a role as a habitat for three tropical biota groups (Murphy, et al., 1998; Wratten, et al., 1998 in Rahman, 2010). Habitat is the place of a living organism or can also indicate a place occupied by the entire community. Begon et al. (1986) in Rahman (2010) argues that an area as a habitat (habitable area) is an area for each species in it, can maintain the existence of its population because (1) has the opportunity to colonize, and (2) is not defeated by competitors . While the potential of various wild plants / weeds as refugia plants for some natural enemies of pests in the plantation area or the system is still limited in information so that the community in particular, in Kerongkong Village East Lombok Regency is in dire need of information related to wild plants as Refugia Predator and Parasitoid. Furthermore, research on Identification of Wild Plants as Refugia Predators and Parasitoid Citrus Plants (Citrus grandis) in Kebun Jeruk Kerongkong Village, East Lombok Regency aims to provide information for the community and as a literature review in studying Wild Plants as Predator and Parasitoid Refugia. The output target desired by the researcher is to provide information and add and as a literature review of wild plants as Refugia Predator and Parasitoid for the community, students and researchers, therefore Descriptive methods are used to identify Wild plants as Refugia Predator and Parasitoid, where the scope of the type of descriptive research is to be able to find various data and facts from the object of research, as well as describe or describe, or describe and explain, in accordance with the sequence of problems presented.